2021
DOI: 10.1088/1361-6463/ac2cac
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructure nanocomposite with local surface plasmon resonance effect enhanced photocatalytic activity—a critical review

Abstract: The unique characteristics of the local surface plasmon resonance (LSPR) effect endows heterostructure nanocomposite of noble metal (NM) nanoparticles and semiconducting materials with dramatically enhanced light absorption, charge separation and surface activity. In addition, they boost the development of research in photocatalytic fields including artificial photosynthesis, degradation of pollutants and deactivation of microorganisms. The advantages of using LSPR to improve the photocatalytic activity of sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 208 publications
0
13
0
Order By: Relevance
“…Therefore, ROS may be the main cause of death in PWNs. Research has shown that most nanoparticles produce ROS through LSPR 34,35 . In this study, the LSPR of SeNPs@CS was shown through UV–vis spectroscopy.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, ROS may be the main cause of death in PWNs. Research has shown that most nanoparticles produce ROS through LSPR 34,35 . In this study, the LSPR of SeNPs@CS was shown through UV–vis spectroscopy.…”
Section: Resultsmentioning
confidence: 80%
“…Research has shown that most nanoparticles produce ROS through LSPR. 34,35 In this study, the LSPR of SeNPs@CS was shown through UV-vis spectroscopy. This study further revealed the process of SeNPs@CS entering the PWNs.…”
Section: Analysis Of Oxygen Free Radicals (Ros)mentioning
confidence: 89%
“…Metal NPs can produce robust local electric fields on their surface with a frequency close to their plasmon resonance frequency under light irradiation. The intensity of the electric field of local plasmonic “hot spots” is almost 1000 times larger than the incident electric field, as calculated by electromagnetic simulations using the finite-difference time-domain (FDTD) method [ 64 , 65 ]. Thus, the rate of generation of e − – h + pairs in these “hot spot” regions is 1000 times higher than the incident electromagnetic field.…”
Section: Plasmonic Effect For Photocatalytic Degradationmentioning
confidence: 99%
“…The heat then first causes the metal lattice to vibrate and heat up by electron–phonon interaction and is later released to the surrounding medium by phonon–phonon interaction. The duration of this process is in the nanosecond range [ 64 , 76 ]. It is important to point out that the plasmonic photothermal effect has many advantages over conventional heating techniques: (1) the heating rate of the plasmonic photothermal effect is fast, which can improve the performance of the photocatalyst, (2) the selective heating of the plasmonic metal NPs maintains the action of the catalysts and prevents the heating of the surrounding medium during the reaction, since most of the reaction takes place at the catalyst surface, which saves energy, and (3) by adjusting various properties of the plasmonic metal NPs, the heating conditions and the performance of the catalyst can be controlled [ 77 79 ].…”
Section: Plasmonic Effect For Photocatalytic Degradationmentioning
confidence: 99%
“…3 Light irradiation-induced plasma oscillation. 70 Catalysis Science & Technology Perspective based on catalysts with the LSPR effect are being extensively investigated.…”
Section: Catalysis Science and Technology Perspectivementioning
confidence: 99%